(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The journey towards women’s freedom in India has been complex and multifaceted, encompassing legal, social, economic, and political dimensions. Despite significant progress over the past decades, numerous challenges persist. This paper explores the historical context, current status, challenges, and future prospects of women’s freedom in India. The study also includes a comparative analysis of key indicators of women’s freedom in India with other countries.